Regulation of Human Innate Lymphoid Cells in the Context of Mucosal Inflammation - Schulz-Kuhnt, Anja; Wirtz, Stefan; Neurath, Markus F.; Atreya, Imke (Frontiers in Immunology, 2020)
Since their identification as unique cell population, innate lymphoid cells (ILCs) have revolutionized our understanding of immune responses, leaving their impact on multiple inflammatory and fibrotic pathologies without doubt. Thus, a tightly controlled regulation of local ILC numbers and their activity is of crucial importance. And even though this has been extensively studied in murine ILCs in the last years, our knowledge on human ILCs is still lagging behind. Our review article will therefore summarize recent insights into the function of human ILCs and in particular focus on their regulation under inflammatory conditions. The quality and intensity of ILC involvement into local immune responses at mucosal sites of the human body can potentially be modulated via three different axes: (1) activation of tissue resident mature ILCs; (2) plasticity and local trans-differentiation of specific ILC subsets; and (3) tissue migration and accumulation of peripheral ILCs. Despite a still ongoing scientific effort in this field, already existing data on the fate of human ILCs under different pathologic conditions clearly implicate that all three of these mechanisms are of relevance for the clinical course of chronic inflammatory and autoimmune diseases and might likewise provide new target structures for future therapeutic strategies.